High resolution ultrasound of ophthalmic patients in a tertiary hospital - Hossain, GA; Islam, SM; Mahmood, S; Khan, N; Chakraborty, RK; Talukder, AK (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jan;16(1):50-6.The abstract of this article is available on the PubMed website